A comparison of three supraglottic airway devices used by healthcare professionals during paediatric resuscitation simulation. Issue 9 (17th October 2012) - Schunk, Domagoj; Ritzka, Markus; Graf, Bernhard; Trabold, Benedikt
Abstract : Objective: The aim of this study was to determine the best airway device among the laryngeal mask, I-gel and the laryngeal tube used by healthcare professional groups with different levels of experience with paediatric airway management. Method: Three groups of healthcare professionals were separately provided with brief supervised training in using the three devices. Afterwards the participants were asked to place the airway device. For every participant, the positioning of each device was recorded. The success rate and timing of insertion were measured. Furthermore, each insertion was scored for the ease of insertion, clinical and fibreoptic verification of the position and successful ventilation. Results: A total of 66 healthcare providers (22 paramedics, 22 nurse anaesthetists and 22 anaesthesia residents) participated in the study. The median time of insertion of both the laryngeal mask and the tube was significantly longer than for the I-gel for all professional groups (p<0.001). The success rate with the I-gel was higher than that with the laryngeal mask or tube (p<0.001). Except for the laryngeal mask, there were no differences among the professional groups regarding the fibreoptic evaluation. Conclusions: In terms of both the time required for successful placement and the rate of successful placement, the I-gel is superior to the laryngeal mask and tube in paediatric resuscitation simulations by healthcare professional groups with different levels of experience with paediatric airway management.